SPECIFIC CHARACTERISTICS OF USING PROJECT TECHNOLOGY IN INNOVATIVE EDUCATION - Shukurov Nusrat Narzullaevich (Journals Park Publishing, 2022)
This article covers thoughts and opinions about the Project technology, its content - essence, basic concepts, its types and stages of using the Project technology, and the project annotation created for the purpose of using this technology.
Keywords: Project technology, pedagogy, class, lesson, learner, school, teaching, work, game, student, teacher